Case Report: Alagille Syndrome Presenting with Angioid Streaks. Issue 2 (29th January 2021) - Katsoulos, Konstantinos F.; Kapsala, Zoi; Livir-Rallatos, Gerasimos
Abstract : SIGNIFICANCE: Alagille syndrome is rare genetic disease, which affects liver and heart function. Cases are frequently diagnosed late, and a complete ocular examination aids in the diagnosis. Although ophthalmic manifestations are usually benign, occasionally, sight-threatening complications occur. PURPOSE: The case presented herein highlights a rare condition, which usually can be diagnosed by the ophthalmological findings. However, in this particular case report, the complication of angioid streaks and choroidal neovascularization is reported for the first time in Alagille syndrome. CASE REPORT: Α 32-year-old woman diagnosed with Alagille syndrome presented with diminution of vision in the left eye. The cause was choroidal neovascularization related to angioid streaks. She was treated with intravitreal injections of ranibizumab but developed an extensive macular scar. A few years later, she developed the same complication in the right eye and was treated similarly. CONCLUSIONS: Alagille syndrome has many ophthalmic manifestations, most of them benign with minimal threat to vision. Herein for the first time, we present a case of Alagille syndrome with angioid streak–related choroidal neovascularization, which resulted in severe vision loss.